The effect Benefit PZ biostimulant on the fruit size and yield production of apricot varieties (Prunus Armeniaca) - Drén, Gábor; Dani, Mária; Racskó, József; Thurzó, Sándor (Acta Agraria Debreceniensis, 2006)
Fruit size is determined by the genetic makings of varieties the pomology and enviromental factors. The climate and the previous year’s harvested yield have a great effect on yield volume. It is not easy to harmonize the qualitative and quantitave parameters of the fruit. High yield usually causes smaller fruits. The aim of our trials was to evalaute the effect of Benefit PZ biostimulant on fruit size. We examined two apricot varieties (Bergeron, Magyarkajszi C235) for the efficacy of the product. The three applications were made with 400 l/ha water with 2500 ppm. The optimal interval of application with Benefit PZ is during in the early phases of development. The size of the final fruits depends on the number of cells making up the fruits. The later application could not increase fruit size growth, there are no significant differences between the Benefit PZ sprayed and the control plots. The totally harvested fruit weight was 13.5% more on the trees of cv. Bergeron, it was caused by the higher fruit set. On the sprayed trees were 12.2% more fruit. Therefore were no differences between the average fruit weight. Fruit weights of the treated trees were 44.37 g on cv. Bergeron, 44.15 g on cv. Magyarkajszi C235 and on the no treated trees were 43.83 g as well as 45.33 g.